2002
DOI: 10.3758/bf03192834
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent-chain performance in transition: Effects of terminal-link duration and individual reinforcers

Abstract: Pigeons responded on concurrent-chain schedules with variable-interval initial links and equal delays as terminal links. The terminal-link delays were 1 sec in some conditions and 20 sec in other conditions. The percentages of reinforcers delivered for responses on the left key were 10%, 30%, 70%, or 90%, and this percentage was switched every five to nine sessions. The rate of change in the pigeons' response percentages after a switch was the same whether the terminal-link delays were 1 sec or 20 sec. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The reason for the apparent discrepancy is that Grace (2002a) used a design in which the schedules preceding and following the reversal were manipulated factorially, so that their effects could be assessed independently. According to the LINOP model, when the durations preceding and following the transition are the same, as in Mazur's (2002) study, their effects cancel out. Thus, the LINOP model is able to account for the results in both Grace's and Mazur's studies.…”
Section: Investigated Whethermentioning
confidence: 69%
See 3 more Smart Citations
“…The reason for the apparent discrepancy is that Grace (2002a) used a design in which the schedules preceding and following the reversal were manipulated factorially, so that their effects could be assessed independently. According to the LINOP model, when the durations preceding and following the transition are the same, as in Mazur's (2002) study, their effects cancel out. Thus, the LINOP model is able to account for the results in both Grace's and Mazur's studies.…”
Section: Investigated Whethermentioning
confidence: 69%
“…In his experiment, the terminal-link delays were equal (1 or 20 sec), and the percentage of terminal-link entries provided by the initial links was changed across conditions. Overall, Mazur (2002) found no effect of terminal-link duration on acquisition. Although initiallink response rates were much higher when the terminallink delays were 1 sec, the rate of change in preference was the same as in the 20-sec condition.…”
Section: Investigated Whethermentioning
confidence: 76%
See 2 more Smart Citations
“…Mazur et al found that preference adapted more rapidly when the proportion of entries arranged by the initial links was changed rather than when the terminal-link delays were changed. Mazur (2002a) studied whether acquisition of initial-link preference depended on overall terminal-link duration. In his experiment, terminal-link delays were equal (1 second or 20 seconds), and the proportion of terminal-link entries arranged by the initial links was changed.…”
Section: Acquisition In Concurrent Chainsmentioning
confidence: 99%